2021
DOI: 10.1016/j.bioactmat.2021.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive glass promotes the barrier functional behaviors of keratinocytes and improves the Re-epithelialization in wound healing in diabetic rats

Abstract: Upon skin injury, re-epithelialization must be triggered promptly to restore the integrity and barrier function of the epidermis. However, this process is often delayed or interrupted in chronic wounds like diabetic foot ulcers. Considering that BG particles can activate multiple genes in various cells, herein, we hypothesized that bioactive glass (BG) might be able to modulate the barrier functional behaviors of keratinocytes. By measuring the transepithelial electrical resistance (TEER) and the paracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…COL I, FN 1 and Lam were produced by fibroblasts, as vital proteins in the extracellular matrix to regulate wound contraction. 38 OCL and ZO-1 also play an essential role in normal cell differentiation and connection, 39 their levels improved in the dSCP group. However, RT-PCR results showed that the content of related genes was the highest when the concentration of dSCP was 50 μg mL −1 , and decreased at 100 μg mL −1 (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…COL I, FN 1 and Lam were produced by fibroblasts, as vital proteins in the extracellular matrix to regulate wound contraction. 38 OCL and ZO-1 also play an essential role in normal cell differentiation and connection, 39 their levels improved in the dSCP group. However, RT-PCR results showed that the content of related genes was the highest when the concentration of dSCP was 50 μg mL −1 , and decreased at 100 μg mL −1 (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Bioactive glass nanoparticles (BGN) are a unique class of biomaterials that have demonstrated the great potential in the field of skin tissue regeneration as they are able to accelerate the re-epithelization [ 13 ], enhance the angiogenesis [ 14 ] and modulate the inflammatory responses [ 15 ]. Additionally, BGN has also been reported to be biodegradable during the tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…JAM-A knockdown promotes keratinocyte proliferation and migration to improve the skin healing process in vivo , regulated by the signaling of FAK-mediated Erk1/2 activation ( Wang et al, 2018 ). Bioactive glass (BG) extracts a posttranscriptional regulation mechanism on the expression of JAM-A to assemble into TJs located along the edge of the cell membrane, involved in mediating the enhanced barrier function of the keratinocyte monolayers ( Tang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%